ANALISIS KESIAPAN OPERASIONAL IMPLEMENTASI REDISPATCH UNTUK MENDUKUNG PENINGKATAN PAYLOAD PADA PENERBANGAN GARUDA INDONESIA - Fikri Kawakibi H, Muhammad
This final project discusses the analysis of Garuda Indonesia airline training program preparation and procedure manual to carry out flight operations with redispatch flight plan. This operating method is proposed by Garuda Indonesia to maximize the potential payload that can be carried by reducing the fuel load required in the flights in accordance with the reference regulations, especially CASR 121 and OpSpecs B44. Calculation analysis is carried out to determine the optimal POR, initial destination, alternate airport, and payload increase for each flight that will implement the operating procedure. The analysis is carried out by means of a literature study to summarize comprehensive concepts and procedures for redispatching, then comparing Garuda Indonesia airline’s training programs and procedure manuals to do redispatch with the requirements of the regulations that are referenced. If the Garuda Indonesia training program and manual procedures are ready and fulfilling the requirements according to the regulations, the optimal POR, initial destination, and alternate airport calculations would be performed. The optimal POR is calculated by entering the waypoints distance on the flight plan that is predicted to produce the largest payload increase to an Excel graph, then calculating the payload increase that can be generated by each waypoints. After choosing the most optimal waypoint as POR, the optimal initial destination is selected based on the airports that are on the route to the intended destination that has the top of descent closest to the POR. Finally, alternate airport is selected by determining the airport that has a distance from the POR that is closer than, but close to the distance from the POR to the initial destination. Optimal payload increase is calculated by entering fuel requirements in the normal flight plan and redispatch flight plan into Excel, then comparing the potential benefits and savings that redispatch flights can achieve prior to normal flight operations between redispatch flight payload variations in each routes and types of aircraft.? In the redispatch procedure, the aircraft is carrying two flight plans, namely the flight plan to the airport that is closer than the destination airport or initial destination, and to the actual destination or intended destination. The aircraft carries fuel according to the needs to reach the initial destination. At a flight point before the initial destination, point of redispatch (POR), the flight crew will ensure that the remaining fuel and meteorological conditions in the air are enough to reach the intended destination. If the aircraft does not allow to continue to the intended destination, the aircraft will land to refuel in the initial destination. If the flight is decided to land on the initial destination, the pilot in command (PIC) will perform divert procedure with reference to SOP 330.330.05. Based on the evaluation of the Garuda Indonesia airline's training procedures and manual procedures to redispatch to meet the regulations, Garuda Indonesia fulfilled the requirements according to regulations. Based on the calculation of the relationship between increased payload and redispatch point location for Jeddah-Jakarta flights, the most optimal POR is located at PAGAI waypoint. For Jakarta-Amsterdam flights, the most optimal POR is located at the DEGET waypoint. Hang Nadim International Airport is determined as the initial airport for Jeddah-Jakarta redispatch flights, and for Jakarta-Amsterdam redispatch flights, Frankfurt International Airport is determined as the initial airport. Changi International Airport, Singapore is determined as alternate airport for Jeddah-Jakarta redispatch flights. For Jakarta-Amsterdam redispatch flights, Munich International Airport is designated as the alternate airport. Redispatch flights are optimal when payload is increased to the MTOW limit, or RTOW if it is smaller than MTOW, except for the Jeddah-Jakarta route that uses the Boeing 777-300ER. For the Jeddah-Jakarta route that uses the Boeing 777-300ER, the most optimal payload increase is up to 90% MTOW.